ESTABLISHING INTERACTION WITH STAKEHOLDERS AS A PREREQUISITE FOR THE FORMATION OF BUSINESS ECOSYSTEM OF ENERGY ENTERPRISES - Polyanska, Alla Stepanivna; Мартинець, Володимир Богданович; Мельничук, Іван Володимирович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The preconditions and features of the formation of the business ecosystem of energy enterprises are considered. The components of the environment of formation of the business ecosystem of the enterprise are characterized and schematically presented. The semantics of the concept of "business ecosystem" is determined on the basis of consideration of such its components as "business" and "eco-system". The place and role of interaction of stakeholders in the formation of the business ecosystem of the enterprise is substantiated on the basis of determining the current relationships and their areas of potential expansion based on promising areas and ways to reform the energy sector in Ukraine. Emphasis is placed on those areas of development that meet the challenges of environmental protection and require the expansion of partnership, as well as the development of new areas of cooperation within the existing interaction. An example of the formation of a business ecosystem for the object of NJSC “Naftogaz of Ukraine” on the basis of research and characteristics of the interaction of stakeholders of the enterprise is considered. It is concluded that the formation of the business ecosystem of the enterprise in the energy sector is an activity aimed at uniting the efforts of all participants in creating a supply chain of energy resources, whose activities, on the one hand, aims to achieve business goals, meet energy needs. resources of different consumer groups, and on the other - compliance with conditions that ensure the balance of their activities, which is achieved by creating conditions to achieve sustainable development goals and developing measures to maintain the ability of ecosystems to maintain their structure and functionality under external factors. The main directions of work of the enterprises which are considered as a precondition of formation of business ecosystem are allocated. The principles of establishing the interaction of stakeholders, which are transformed into the principles of forming a business ecosystem, are proposed.